Calla palustris (Water Arum, Wild Calla) : Water Arum, Wild Calla - (L.) Scop. (Author); Veronica Speers (Collector); R. Dickinson (Expert) (2008)
Class: Monocotyledoneae Family: Araceae Genus: Calla Species: palustris